Transformation and Duality of Religious Authority in The Digital Era - Ulil Abdillah (Social Journal of Studies in Education, 2025)
This study examines the shift in religious authority amidst the dominance of social media and the post-truth era. Religious authority, which was once singular and static, now faces the challenges of democratization and fragmentation. Using descriptive qualitative methods and theoretical perspectives ranging from Marshall McLuhan to Bryan S. Turner, this study analyzes the interaction between technology and tradition. The results show that social media has transformed religious authority into a competitive actor in the public arena through digital indicators such as followers, likes, and shares. This phenomenon has triggered the emergence of "Celebrity Ustadz" who often displace traditional ulama due to their expertise in managing algorithms and emotional narratives. In the post-truth era, objective facts tend to be defeated by personal sentiment, forcing authority holders to choose between the depth of knowledge or the relevance of digital aesthetics. In conclusion, social media creates a new ecosystem that redefines religious authority as a "brand" in a highly competitive digital identity market